2018
DOI: 10.11648/j.aff.20180702.12
|View full text |Cite
|
Sign up to set email alerts
|

Prospects of Cage Fish Farming in South Western Uganda

Abstract: The study was conducted to identify the constraints and potential opportunities of cage fish farming in South Western Highland Agro-Ecological Zone (SWHAEZ). 82 questionnaires were administered to six respondent groups (current cage fish farmers, potential adopters of cage aquaculture, farmers who have abandoned cage aquaculture, regional and district fisheries officers, and financial institutions) to obtain insight into the challenges in cage fish farming as well as opportunities that can be exploited to prom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 2 publications
(3 reference statements)
0
1
0
Order By: Relevance
“…These findings are consistent with the findings of Aswathy (2019) which reported that fish cage farming is profitable. Kwikiriza (2018), in a study of the prospects of fish cage culture in Uganda, also reported similar findings. Several studies on aquaculture in Kenya have also reported that fish cage culture is a profitable business (Aura et al., 2018; Munguti, Obiero, et al., 2021; Musa et al., 2021; Mwainge et al., 2021; Njiru et al., 2019; Orina et al., 2018).…”
Section: Discussionmentioning
confidence: 58%
“…These findings are consistent with the findings of Aswathy (2019) which reported that fish cage farming is profitable. Kwikiriza (2018), in a study of the prospects of fish cage culture in Uganda, also reported similar findings. Several studies on aquaculture in Kenya have also reported that fish cage culture is a profitable business (Aura et al., 2018; Munguti, Obiero, et al., 2021; Musa et al., 2021; Mwainge et al., 2021; Njiru et al., 2019; Orina et al., 2018).…”
Section: Discussionmentioning
confidence: 58%